Does increased construction activity transmit into housing prices and rents? Evidence from the V4 countries and Austria - Kadeřábková, Božena; Řežábek, Pavel (Frontiers in Sustainable Cities, 2023)
We analyze the housing prices and their sensitivenes to selected variables, especially regarding construction activity in the V4 countries and Austria.By employng a specification of a recursive VAR model for each country, we show that the most responsive to changes in construction activity is housing market in Austria. Meanwhile housing prices in the V4 countries do not exhibit any strong assocition with construction activity, perhaps due to undersupply of housing in the countries.